2005
DOI: 10.1097/01.alc.0000166944.79914.0a
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Activation of Myosin Light Chain Kinase Leads to Dysfunction of Tight Junctions and Blood-Brain Barrier Compromise

Abstract: These results suggest that EtOH activates MLCK leading to phosphorylation of MLC, occludin and claudin-5. Cytoskeletal alterations (MLC) and TJ changes (occludin and claudin-5 phosphorylation) result in BBB impairment (decrease in TEER). TJ compromise is associated with increased monocyte migration across the BBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
141
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(165 citation statements)
references
References 64 publications
20
141
1
3
Order By: Relevance
“…Our results suggest that PKCε's role in metastasis may be related to its ability to impair the barrier function (and cell adhesion) through phosphorylation of TJ proteins such as claudin-4. These findings are consistent with a number of studies that have previously shown that phosphorylation of various claudin proteins can decrease TJ integrity [32,35,[51][52][53][54], although phosphorylation of claudin-1 has also been shown to promote barrier function [29,31]. However, it is important to note that TJ disruption likely occurs through multiple mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…Our results suggest that PKCε's role in metastasis may be related to its ability to impair the barrier function (and cell adhesion) through phosphorylation of TJ proteins such as claudin-4. These findings are consistent with a number of studies that have previously shown that phosphorylation of various claudin proteins can decrease TJ integrity [32,35,[51][52][53][54], although phosphorylation of claudin-1 has also been shown to promote barrier function [29,31]. However, it is important to note that TJ disruption likely occurs through multiple mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…BBB showed edema and abnormal mitochondria (Karwacka, 1980). Partial disruption of the BBB and increased nonspecific paracellular permeability are also consistent with the observation in vitro that alcohol treatment activates myosin light chain kinase, alters the distribution and function of the tight junction proteins occludin and claudin-5, and reduces transendothelial electrical resistance (Haorah et al, 2005a).…”
Section: Discussionsupporting
confidence: 85%
“…Further studies will investigate this in more detail. MLC phosphorylation in endothelial cells induces transient cytoskeletal reorganization, cell retraction, and conformational changes in tight junction proteins that can conceal immunoreactive epitopes and inhibition of MLC kinase prevents hypoxia-induced opening of the BBB in vitro (Wysolmerski and Lagunoff, 1990;Haorah et al, 2005;Kuhlmann et al, 2007). This cascade could explain the severe but transient loss of immunoreactive claudin-5 in vehicle-treated mice and the hyper-acute MMP-9-independent phase of disruption in IL-1␤-challenged mice.…”
Section: Discussionmentioning
confidence: 99%